2012
DOI: 10.1108/02621711311286892
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and knowledge management in UK ICT organisations

Abstract: Purpose -While it is well known that leadership can play an important role in engendering effective knowledge management activity, relatively little is known about which styles of leadership are most appropriate for this task. The purpose of this paper is to contribute to theory by exploring dimensions of leadership as presented by Avolio and Bass (Transformational, Transactional and Passive-Avoidance Leadership) and the dimensions of organisational knowledge management activity as presented by Maier and Mosle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 27 publications
6
46
3
Order By: Relevance
“…The business shows enormous capitals and the highly hybrid organization. Analoui et al (2012) indicated that a successful innovator could have innovation become an important strategy in a business. Innovation strategies revealed the abilities to develop and commercialize products, services, and organizational systems, including new production techniques or new product and service distribution.…”
Section: Competitive Advantagesmentioning
confidence: 99%
“…The business shows enormous capitals and the highly hybrid organization. Analoui et al (2012) indicated that a successful innovator could have innovation become an important strategy in a business. Innovation strategies revealed the abilities to develop and commercialize products, services, and organizational systems, including new production techniques or new product and service distribution.…”
Section: Competitive Advantagesmentioning
confidence: 99%
“…García-Morales et al (2012) defined new products as a product which a business did not have before, regardless whether there was such a product in the market. For certain products, businesses, or countries, Analoui et al (2012) indicated that either a globally new product or the improvement of an existing product could be regarded as a new product. Jiménez-Jiménez and Sanz-Valle (2011) considered new products as new things for a business, market, or industry, which could profit the customers.…”
Section: Product Innovation Typementioning
confidence: 99%
“…The product innovation type is divided into radical innovation and incremental innovation in this study. Analoui et al (2012) defined new products as "new products for a company", including unprecedented products, quality, and package modification, imitating existing products of competitors, introducing foreign products for the first time, and adding "new" ideas to all product composition. New products were those most customers in a certain market considered as "new".…”
Section: Product Innovation Typementioning
confidence: 99%
See 1 more Smart Citation
“…11, No. 6;2016 Set of practices that help achieving the strategic fit inside the organization through knowledge creation, sharing and discrimination knowledge by using the electronic messages and non-electronic messages such as: using the memos, meetings and e-mail (Analoui et al, 2013). …”
Section: It Is Possible To Mention Some Of Knowledge Management Definmentioning
confidence: 99%